Beneficial effect of corticosteroids in preventing mortality in patients receiving tocilizumab to treat severe COVID-19 illness. (December 2020) - Rubio-Rivas, Manuel; Ronda, Mar; Padulles, Ariadna; Mitjavila, Francesca; Riera-Mestre, Antoni; García-Forero, Carlos; Iriarte, Adriana; Mora, Jose M.; Padulles, Nuria; Gonzalez, Monica; Solanich, Xavier; Gasa, Merce; et al.
Highlights: Dexamethasone or alternative steroids are recommended in severe COVID-19 cases. The use of tocilizumab in COVID-19 cases, with or without steroids, is still controversial. Risk for mortality was assessed in 186 COVID-19 patients receiving tocilizumab. Mortality was associated with older age, chronic heart failure, and liver disease. In tocilizumab-treated patients, the additional use of steroids was beneficial. Abstract: Objectives: To assess the characteristics and risk factors for mortality in patients with severe coronavirus disease-2019 (COVID-19) treated with tocilizumab (TCZ), alone or in combination with corticosteroids (CS). Methods: From March 17 to April 7, 2020, a real-world observational retrospective analysis of consecutive hospitalized adult patients receiving TCZ to treat severe COVID-19 was conducted at our 750-bed university hospital. The main outcome was all-cause in-hospital mortality. Results: A total of 1, 092 patients with COVID-19 were admitted during the study period. Of them, 186 (17%) were treated with TCZ, of which 129 (87.8%) in combination with CS. Of the total 186 patients, 155 (83.3 %) patients were receiving noninvasive ventilation when TCZ was initiated. Mean time from symptoms onset and hospital admission to TCZ use was 12 (±4.3) and 4.3 days (±3.4), respectively. Overall, 147 (79%) survived and 39 (21%) died. By multivariate analysis, mortality was associated with older age (HR = 1.09, p < 0.001), chronic heart failure (HR = 4.4, p = 0.003), and chronic liver disease (HR = 4.69, p = 0.004). The use of CS, in combination with TCZ, was identified as a protective factor against mortality (HR = 0.26, p < 0.001) in such severe COVID-19 patients receiving TCZ. No serious superinfections were observed after a 30-day follow-up. Conclusions: In patients with severe COVID-19 receiving TCZ due to systemic host-immune inflammatory response syndrome, the use of CS in addition to TCZ therapy, showed a beneficial effect in preventing in-hospital mortality.